Analysis of Rising Fresh Water Cooler Temperature Main Engine KM. Leuser - A Agus Tjahjono; Driaskoro Budi Sidharta; Aditya Romi Satrianto (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2022)
Cooler is a auxiliary engine that functionaly to cooling fresh water on board, cooler usage is very important because the operational of main engine depends the cooler, because for diesel engine the cylinder liner always getting hot after combustion. If the cylinder get no cooling, the oil viscocity will be low and make piston and cylinder damaged. The purpose of this research is to know the problem of unnormaly temperature cooler. To understand the maintenance the trouble fresh water cooler. The method to solve this problem is observation. This method demanded the writter doing observation. The next is interview with first engineer, and looking for data from manual book, main engine journal. The study of this research is about the trouble from fresh water cooling KM. Leuser. With the important of the cooler we have to know the factor that’s make the temperature going up. And the result of the research is unoptimalize heat absorbtion from cooler plate and the stool from sea water filter, after the clean up the cooler is more cool.